PERANCANGAN SISTEM INFORMASI ABSENSI KARYAWAN BERBASIS WEB PADA PT. MANDIRI CIPTA SEJAHTERA - Irfanuddin Irfanuddin; Ina Maryani (Jupiter: Journal of Computer & Information Technology, 2023)
Internet technology is needed to get information faster. One of the information technology is used to carry out employee attendance activities. PT. Cipta Mandiri Sejahtera (Morena Rent), a the company engaged in car rental, carries out attendance activities for its employees. Morena Rent takes attendance using a fingerprint machine. However, employee fingerprints are sometimes not detected, the attendance data storage is full, and queues occur when employees gather to take attendance, therefore a computerized system is needed that can solve the problem. The method used for this research is to use the Waterfall model using the PHP and MYSQL programming languages. Web testing is carried out using a black box. The results of this research are to design and build a web-based information system program that is expected to reduce system absence problems. With this website, it is hoped that employees can input absences properly without any more errors, making it easy for the admin to process absence data and leave requests.